TO THE FAUNA OF PREDATORY HEMIPTERA (HETEROPTERA) OF SOUTH-EASTERN KAZAKHSTAN (Experimental biology, 2021)
The Hemiptera, or bugs, are the largest order of insects with incomplete metamorphosis. The main part of hemiptera is terrestrial, they live in the soil, on various parts of plants, in the forest floor, etc. Among them there are many species of carnivorous or mixed food, but herbivorous forms predominate; periodically multiplying in large numbers, they cause significant damage to forest and agricultural crops. Some of the Hemiptera, being the predators that destroy the pests of agriculture and forestry. The research was conducted in 2019-2020 in various biotopes of South-Eastern Kazakhstan. Various methods were used to collect insects: catching insects was carried out with a standard entomological net, small insects with an exhauster, manual collection, catching in the light, etc. As a result of the conducted research, 32 species of predatory hemiptera from 5 families were identified in the study region. Among them, the species diversity is dominated by representatives of the family Nabidae – 11 species (34%), Anthocoridae – 7 species (23%), Pentatomidae – 6 species (22%), and from the families. Reduviidae and Miridae – 4 species each (12% each). According to ecological features, the following groups are distinguished: xerophiles (3 species, 9%), mesophiles (28 species, 87%) and hygrophiles (1 species, 4%). According to life cycles, all species of predatory hemiptera of South-Eastern Kazakhstan are divided into 3 groups: monovoltine species – 24 (76%), bivoltine – 4 (12%), polyvoltine – 2 (6%), the number of generations is unknown - 2 species (6%). They are dominated by species wintering in the imago stage (22 species, 69%), in the imago and larval stage (2 species, 6%), in the egg stage (8 species, 25%). Picromerus lewisi Scott, 1874 was recorded in Kazakhstan for the first time.Key words: fauna, predatory hemiptera, South-Eastern Kazakhstan.